Evaluation of Bifidobacteria and Lactobacillus Probiotics as Alternative Therapy for Salmonella typhimurium Infection in Broiler Chickens - Hanem El-Sharkawy; Amin Tahoun; Amira M. Rizk; Tohru Suzuki; Walid Elmonir; Eldsokey Nassef; Mustafa Shukry; Mousa O. Germoush; Foad Farrag; May Bin-Jumah; Ayman M. Mahmoud (Animals, 2020)
Chicken Salmonella enterica serovars are enteric bacteria associated with massive public health risks and economic losses. There is a widespread antimicrobial resistance among S. enterica serotypes, and innovative solutions to antibiotic resistance are needed. We aimed to use probiotics to reduce antibiotic resistance and identify the major probiotic players that modify the early interactions between S. enterica and host cells. One-day-old cobb broiler chicks were challenged with S. typhimurium after oral inoculation with different probiotic strains for 3 days. The adherence of different probiotic strains to Caco-2 intestinal epithelial cells was studied in vitro. Lactobacillus (Lacticaseibacillus) casei ATTC334 and Bifidobacterium breve JCM1192 strains attached to Caco-2 cells stronger than B. infantis BL2416. L. casei ATTC334 and B. breve JCM1192 reduced S. typhimurium recovery from the cecal tonsils by competitive exclusion mechanism. Although B. infantis BL2416 bound poorly to Caco-2 epithelial cells, it reduced S. typhimurium recovery and increased IFN-γ and TNF-α production. L. casei ATTC334, B. breve JCM1192 and B. infantis BL2416 improved body weight gain and the food conversion rate in S. typhimurium-infected broilers. B. longum Ncc2785 neither attached to epithelial cells nor induced IFN-γ and TNF-α release and consequently did not prevent S. typhimurium colonization in broiler chickens. In conclusion, probiotics prevented the intestinal colonization of S. typhimurium in infected chickens by competitive exclusion or cytokine production mechanisms.